2014
DOI: 10.1590/s1984-29612014001
|View full text |Cite
|
Sign up to set email alerts
|

Studies on coccidian oocysts (Apicomplexa: Eucoccidiorida)

Abstract: The oocysts of the coccidia are robust structures, frequently isolated from the feces or urine of their hosts, which provide resistance to mechanical damage and allow the parasites to survive and remain infective for prolonged periods. The diagnosis of coccidiosis, species description and systematics, are all dependent upon characterization of the oocyst. Therefore, this review aimed to the provide a critical overview of the methodologies, advantages and limitations of the currently available morphological, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
68
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 120 publications
(71 citation statements)
references
References 97 publications
0
68
0
3
Order By: Relevance
“…The oocysts were quantified as estimates of the number of oocysts per fecal drop (OPD), for which the total number of oocysts recovered from defecation was counted on a microscope slide, in accordance with the guidelines of Dolnik (2006). The oocysts were identified at 1000x magnification based on the guidelines for morphological and morphometric studies of Duszynski & Wilber (1997) and Berto et al (2014b).…”
Section: Methodsmentioning
confidence: 99%
“…The oocysts were quantified as estimates of the number of oocysts per fecal drop (OPD), for which the total number of oocysts recovered from defecation was counted on a microscope slide, in accordance with the guidelines of Dolnik (2006). The oocysts were identified at 1000x magnification based on the guidelines for morphological and morphometric studies of Duszynski & Wilber (1997) and Berto et al (2014b).…”
Section: Methodsmentioning
confidence: 99%
“…All measurements were made in micrometers and are given as the range followed by the mean in parentheses. The descriptions of oocysts and sporocysts followed the guidelines of Duszynski & Wilber (1997) and Berto et al (2014), as follows: oocyst (O) length (L) and width (W) and their ranges and ratios (L/W); micropyle (M), oocyst residuum (OR), polar granule (PG) and sporocyst (SP) length (L) and width (W) and their ranges and ratios (L/W); and Stieda body (SB), sub-Stieda body (SSB), para-Stieda body (PSB), sporocyst residuum (SR), sporozoite (SZ), refractile body (RB) and nucleus (N).…”
Section: Methodsmentioning
confidence: 99%
“…Genus Caryospora Leger, 1904, is occasionally reported in raptors and reptiles, which act as its definitive hosts, and in rodents, which act as its intermediate hosts (UPTON et al, 1990;BERTO et al, 2014). Caryospora is the third largest genus in the family Eimeriidae.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Caryospora Leger, 1904, is traditionally recognized as one of the main genera of coccidian parasites of both raptors and reptiles (UPTON et al, 1990;BERTO et al, 2014). Hence, the species of Caryospora that have been recorded in raptors were recently taxonomically transferred to a new genus, termed Avispora Schuster, Woo, Poon, Lau, Sivakumar, Kinne, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…This reclassification was based on the morphological, biological and, finally, molecular differences of Caryospora spp. found in raptors and reptiles (BERTO et al, 2014;SCHUSTER et al, 2016) In this context, the current study describes a new species of Avispora found in little owls (A. noctua) that were being kept for rehabilitation and reintroduction into the wild at the Lisbon Center for Wild Animal Recovery (Centro de Recuperação de Animais Silvestres de Lisboa, LxCRAS), in Monsanto Forest Park, Lisbon, Portugal.…”
Section: Introductionmentioning
confidence: 99%